Vitamin D fortification of eggs alone and in combination with milk in women aged 44–65 years - Vičič, Vid (Zdravstveno varstvo, 2023)
Introduction: For almost nine decades, the fortification of foods with vitamin D has been proven effective in preventing rickets. This study aims to build and economically evaluate a fortification model based on egg biofortification and milk (including yoghurt) fortification. Methods: A cross-sectional study was carried out between 1. March and 31. May 2021. Three hundred and nineteen healthy women from the Central Slovenian region aged between 44 and 65 were recruited for the study, with 176 participants included in the final analysis. For the fortification model calculations, the vitamin D contents of unenriched milk (including yoghurt) and eggs were replaced by enriched foods containing vitamin D. The economic evaluation was done using available drug and food supplement prices. Fortification costs were calculated using vitamin D prices provided by suppliers.Results: Mean vitamin D intake from food was 2.19±1.34 µg/d. With fortification Model 1 (enriched eggs), it would be: 6.49±4.45 µg/d, and with Model 2 (enriched eggs and milk): 10.53±6.49 µg/d. Without fortification, none of the participants would reach a daily vitamin D intake >10 µg. With fortification Model 1 (egg fortification), 15.3% would reach >10 µg and with Model 2 (egg and milk fortification) 46.2% would reach >10 µg. The economic comparison of the annual cost of 10 µg vitamin D/d/person was EUR 6.17 for prescription drugs, EUR 6.37 for food supplements, EUR 0.09 for direct milk fortification and EUR 0.12 for egg biofortification with vitamin D.Conclusions: Egg and milk (including yoghurt) fortification could cost-effectively increase vitamin D intake in the Slovenian population of women between 44 and 65 by almost five-fold, and could significantly lower the prevalence of vitamin D deficiency. Additional research and changes to legislation are needed before this can be introduced.
Keywords: economic evaluation; ekonomsko vrednotenje; post-menopausal women; pre-menopausal women; vitamin D; ženske po menopavzi; ženske v predmenopavzi